Housewife's Income Development Program Through Improving Nutrition by Consuming Moringa Vegetable Porridge as an Effort to Overcome Stunting - A'yun, Inarotul; nurlaili, Nurlaili; agustin, Agustin; fitriana, Fitriana; irfandi, Irfandi; rofiq, Ainur (CV. Zabags Qu Publish, 2023)
This service activity was carried out in Mentoro Village, Sokosari District, Tuban Regency, East Java Province on September 5 2023. The method used in this activity was community education and training. This service activity reflects the comprehensive objectives of the community service program which covers nutritional and economic aspects of the Mentoro village community. This includes nutrition education, training in making Moringa vegetable porridge, developing a Moringa vegetable porridge business, impact measurement, and community development. This program can be developed even better by combining socio-cultural elements in its implementation, such as cooking competitions, question-and-answer quizzes about nutrition, and so on.